2021
DOI: 10.1002/adma.202102797
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Thermoelectric Power Factor of 2D Organometal Halide Perovskites by Suppressing 2D/3D Phase Separation

Abstract: Organometal halide perovskites (OHPs) exhibit superior charge transport characteristics and ultralow thermal conductivities. However, thermoelectric (TE) applications of OHPs have been limited because of difficulties in controlling their carrier concentration, which is a key to optimizing their TE properties. Here, facile control of the carrier concentration in Sn‐based OHPs is achieved by developing 2D crystal structures. The 2D OHP crystals are laterally oriented using a mixed solvent, and the morphology and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…The highest PF value we have achieved is about 3.92 μW m −1 K −2 at the doping ratio of 5 mol %. A summary of previously reported PF values as a function of electrical conductivities for 3D and 2D OIHP semiconductors at room temperature (RT), including MAPbX 3 (X denotes the halide ions) ( Haque et al., 2019 ; Long et al., 2019 ; Mettan et al., 2015 ; Tang et al., 2020 ; Wu et al., 2018 ; Xie et al., 2021 ; Xiong et al., 2019 ; Ye et al., 2017 ), MASnI 3 ( Hao et al., 2014 ; Haque et al., 2020a ), (PEA) 2 MA 2 Sn 3 I 10 ( Yang et al., 2021 ), and (4Tm) 2 FASn 2 I 7 ( Hsu et al., 2021 ), is shown in Figure 4 D. It is seen that the PF value we have achieved in (PEA) 2 SnI 4 by SnI 4 doping is among the highest ones ( Hsu et al., 2021 ; Yang et al., 2021 ). It is also notable that Sn-based OIHPs, which generally have higher σ than Pb-based OIHPs, exhibit higher PF values, suggesting that Sn-based OIHPs are very attractive for high-performance TE devices.…”
Section: Resultsmentioning
confidence: 99%
“…The highest PF value we have achieved is about 3.92 μW m −1 K −2 at the doping ratio of 5 mol %. A summary of previously reported PF values as a function of electrical conductivities for 3D and 2D OIHP semiconductors at room temperature (RT), including MAPbX 3 (X denotes the halide ions) ( Haque et al., 2019 ; Long et al., 2019 ; Mettan et al., 2015 ; Tang et al., 2020 ; Wu et al., 2018 ; Xie et al., 2021 ; Xiong et al., 2019 ; Ye et al., 2017 ), MASnI 3 ( Hao et al., 2014 ; Haque et al., 2020a ), (PEA) 2 MA 2 Sn 3 I 10 ( Yang et al., 2021 ), and (4Tm) 2 FASn 2 I 7 ( Hsu et al., 2021 ), is shown in Figure 4 D. It is seen that the PF value we have achieved in (PEA) 2 SnI 4 by SnI 4 doping is among the highest ones ( Hsu et al., 2021 ; Yang et al., 2021 ). It is also notable that Sn-based OIHPs, which generally have higher σ than Pb-based OIHPs, exhibit higher PF values, suggesting that Sn-based OIHPs are very attractive for high-performance TE devices.…”
Section: Resultsmentioning
confidence: 99%
“…Most recently, high S and excellent thermal stability were realized in 2D tin-based perovskites because of their quantum confinement effect and organic ligands, respectively. [15,46] We therefore envision that the surface doping strategy demonstrated in this work, when applied to low-dimensional THPs, may further boost the TE performance.…”
Section: Discussionmentioning
confidence: 99%
“…[11,12] However, the carrier density of THPs is still constrained by the limited capability of accommodating heterogeneous dopants and the heavy compensation from intrinsic defects, both of which severely undermine their TE performances. The studies of THP-based TE materials are rarely reported and have just come to burgeon in recent years, [13][14][15][16] most of which were centered upon diversified doping strategies. Among them, all-inorganic CsSnX 3 perovskites have attracted enormous attention, thanks to their relatively high σ.…”
Section: Introductionmentioning
confidence: 99%
“…For nonconjugated ligands, Yang et al reported the TE performance of PEA-based 2D perovskites and concluded that the carrier concentration can also be controlled by the n number and MACl doping. 60 With extraordinarily high Seebeck coefficients, a much higher PF of 111 μW m −1 K −2 was achieved with n = 2−4 MACl doped PEA 2 MA n−1 Sn n I 3n+1 thin films (Figure 3d−f). The authors attributed the high Seebeck coefficient to the quantum confinement effect.…”
Section: Structuresmentioning
confidence: 95%
“…The resulting thin films also showed robust thermal stability at mild temperature (i.e., at values <313 K) for over 100 h. Above this temperature, thermal dedoping was observed where the carrier concentration decreased, possibly due to the self-healing characteristic of the 2D perovskites. For nonconjugated ligands, Yang et al reported the TE performance of PEA-based 2D perovskites and concluded that the carrier concentration can also be controlled by the n number and MACl doping . With extraordinarily high Seebeck coefficients, a much higher PF of 111 μW m –1 K –2 was achieved with n = 2–4 MACl doped PEA 2 MA n –1 Sn n I 3 n +1 thin films (Figure d–f).…”
Section: Device Applicationsmentioning
confidence: 98%